Kashmir: the nuclear flashpoint - Nath, Birbal (New Delhi Manas Publications, 2014)
The book traces the genesis of subversion and growth of thermo-nuclearism in the sub-continent financed and abetted by Pakistan in the beautiful valley whose charms are delineated by a powerful verbal brush.
Keywords: IPS as an author; Nuclear weapons-Government policy; Diplomatic relations